Acute abdomen as complication of a knee arthroscopy: A case report - Ana, Jurin Martic; Vidanec, Nenad; Smilović, Joško; Mavrić, Matija; Novak, Miljenko; Jambrešić, Petra Mustač (Archives of Surgery and Clinical Research, 2020)
A knee arthroscopy in spinal anaesthesia was performed on a 67 years old male patient. During the procedure the patient was hemodynamically stable, until he suddenly turned pale and started complaining of severe pain in lower abdomen with signs of guarding. The procedure was finished as urgently as possible and after releasing the tourniquet we noticed significant difference in volume of the leg, with redness distal to tourniquet. Urgent lab results were essentially unremarkable and the patient was sent for the urgent radiological diagnostics. CD of the left leg described fluid in the soft tissues of the thigh, scrotum, and abdomen; and the unenhanced CT of the abdomen showed free fluid along the entire femoral shaft of the left thigh, extending towards pelvis and abdomen to perihepatic and perisplenic space, and retroperitoneum, with gas bubbles tracking along anterior aspect of the left thigh into the left retroperitoneum. He was admitted to the ICU, and within few hours all symptoms have resolved and his further recovery was without complications.